(untitled) (Journal of Universal Science Research, 2025)
This thesis explores the cultural and linguistic features of public speaking in Russian and English. It examines how Russian speakers often emphasize emotional appeal and collectivist values, while English speakers tend to prioritize clarity, logic, and individual expression. Through the analysis of public speeches, the study highlights how each language reflects its cultural identity and rhetorical traditions in spoken discourse.